2003
DOI: 10.1136/vr.152.14.419
|View full text |Cite
|
Sign up to set email alerts
|

Human toxocariasis and direct contact with dogs

Abstract: Toxocariasis in man is traditionally thought to be contracted through the ingestion of eggs from contaminated soil. The disease may manifest itself in different syndromes such as ocular larval migrans, visceral larval migrans and covert toxocariasis. This paper assesses the evidence for the soil contamination hypothesis and proposes that direct contact with dogs may provide a better explanation of the epidemiology of the disease. Hair was collected from 60 dogs from various places in Ireland and the UK and exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
89
3
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 21 publications
7
89
3
1
Order By: Relevance
“…CHIEFFI et al 8 and WOLFE et al 37 , reported a higher frequency of infection in individuals who were in contact with dogs. Ownership of dogs is very common in families living in the field, as they use the dogs to assist them with cattle, being considered very good work partners.…”
Section: Discussionmentioning
confidence: 99%
“…CHIEFFI et al 8 and WOLFE et al 37 , reported a higher frequency of infection in individuals who were in contact with dogs. Ownership of dogs is very common in families living in the field, as they use the dogs to assist them with cattle, being considered very good work partners.…”
Section: Discussionmentioning
confidence: 99%
“…Ownership of pets such as dogs or cats and their presence at home is frequently associated with toxocariasis, as mentioned by many authors 5,22,24,28,[34][35][36][37] . However, this fact was not associated with the seropositivity in the studied population (p = 0.107).…”
Section: Discussionmentioning
confidence: 99%
“…By personal information of Western blot producer, their tests detect and confirm also infections caused by T. cati larvae, so it is suggested that some of our Toxocara positive patients could be infected by the eggs of T. cati. It was known that toxocariasis can be contracted through the ingestion of Toxocara eggs from contaminated soil or food but nowadays it is suggested that humans can be infected also by direct contact and than ingestion of emryonated Toxocara eggs in pet's hair (Wolfe and Wright, 2003).…”
mentioning
confidence: 99%